Epidemiology of Nosema spp. in Apis mellifera Colonies in Attica, Greece: Molecular Survey and Risk Factor Analysis - Tsalou, E; Patergiannakis, IS; Pappas, I; Kolygas, M; Lefkaditis , M; Papadopoulos , E; Athanasopoulou , F (Journal of the Hellenic Veterinary Medical Society, 2026)
Nosema disease, caused by microsporidian fungi of the genus Nosema, poses a significant threat to honeybee (Apis mellifera) populations worldwide. This study calculated the prevalence of Nosema species in honeybee colonies in the Attica region of Greece and assessed the impact of various management practices on infection rates. A survey was conducted in 33 apiaries in the Attica region during the spring of 2022. A total of 130 colonies were sampled and analysed using species-specific multiplex Polymerase Chain Reaction targeting the 16S rRNA gene to detect Nosema species. A questionnaire was administered to beekeepers to gather data covering apiary characteristics, hive design, management practices, and clinical observations of nosemosis symptoms. The results revealed a high prevalence (69.2%) of N. ceranae in the sampled colonies, while N. apis or co-infection with both species was not detected. The absence of N. apis aligns with similar findings across Southern Europe, where N. ceranae has largely displaced the formerly dominant N.apis. Statistical analysis identified significant associations between N. ceranae prevalence and certain management factors. Colonies in migratory apiaries had significantly higher infection rates compared to stationary ones. Additionally, hives with screened bottom boards were less frequently infected than those with solid boards, suggesting a potential protective effect through enhanced ventilation and hygiene. Beekeeper occupation was also linked to infection risk: professional beekeepers' colonies exhibited a significantly higher prevalence than those of sideline and hobbyist beekeepers. Importantly, the study found poor agreement between beekeeper-reported symptoms and laboratory-confirmed infections (Kappa = 0.046), indicating that reliance on visual signs alone is insufficient for accurate diagnosis of N. ceranae. This highlights the need for routine molecular diagnostics in colony health management. Overall, this study provides data on N. ceranae prevalence in Attica, Greece, for the first time and underscores the role of management practices in disease transmission. The findings emphasize the need for improved diagnostic awareness and targeted health strategies to mitigate the spread and impact of N. ceranae in Greek apiculture.